Politeness and Impoliteness Strategies in Lecturer-Student Communication Within Cyberpragmatic Chats - Faizal Risdianto; Machfudz Machfudz; Eka Margianti Sagimin; Hanafi Hanafi; Jumanto Jumanto (Journal of Pragmatics Research, 2023)
This qualitative research on Cyberpragmatic attempts to explore the application of politeness and impoliteness principles in student-lecturer internet-mediated communication in English and Indonesian languages at two faculties of Universitas Islam Negeri (UIN) Salatiga. The native speakers' perceptions of those strategies and principles as applied in the online chatroom were also elicited to confirm the descriptive analysis of the utterances. Pragmatic data were taken, categorized, and selected from Whatsapp conversation and email correspondence screenshots between lecturers and students in eight (8) online English Language classes and six (6) classes on Ushul Fiqh subjects at Universitas Islam Negeri (UIN) Salatiga. Additionally, as demonstrated in the screenshots, an online questionnaire was used to elicit data on students' and lecturers' perspectives on the cyberpragmatic activities. The descriptive analysis shows that the students considered the principles of politeness as a prominent aspect of their communicative actions and managed to appropriately applied it in their cyberpragmatic activities. Additional pragmatic features of religious expressions were also used to amplify the politeness effect. Nevertheless, there were some cases where impoliteness principles were used by the students, regardless of their awareness of their pragmatic consequences. The acceptability judgement questionnaire confirmed the level of politeness and impoliteness strategies previously described. Consequently, future research may benefit from this study by exploring other aspects of cyberpragmatics such as ethnicity, gender, and other socio-political aspects, from interdisciplinary perspectives.